2022
DOI: 10.1097/01.hs9.0000843512.62237.dc
|View full text |Cite
|
Sign up to set email alerts
|

S155: Efficacy and Safety Results From Ascembl, a Phase 3 Study of Asciminib vs Bosutinib in Patients With Chronic Myeloid Leukemia in Chronic Phase After ≥2 Prior Tyrosine Kinase Inhibitors: Wk 96 Update

Abstract: Background:Background: Asciminib is the 1st BCR::ABL1 inhibitor to Specifically Target the ABL Myristoyl Pocket (STAMP). In the ASCEMBL primary analysis, asciminib had superior efficacy and better safety/tolerability vs bosutinib (BOS) in patients (pts) with chronic myeloid leukemia in chronic phase (CML-CP) after ≥2 prior tyrosine kinase inhibitors (TKIs). Major molecular response (MMR) rate at wk 24 was 25.5% on asciminib vs 13.2% on BOS; the difference in MMR rates after adjusting for baseline major cytogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…An updated analysis of the study at the European Hematology Association (EHA) 2022 annual meeting confirmed the persistent improvement of MMR at 2 years (2‐year MMR rate 38% with asciminib vs. 16% with bosutinib). However, this did not translate into improved PFS (2‐year PFS 94% vs. 91%) or improved survival (2‐year survival 97% vs. 99%) 118 …”
Section: Management Of Tki Resistancementioning
confidence: 95%
See 1 more Smart Citation
“…An updated analysis of the study at the European Hematology Association (EHA) 2022 annual meeting confirmed the persistent improvement of MMR at 2 years (2‐year MMR rate 38% with asciminib vs. 16% with bosutinib). However, this did not translate into improved PFS (2‐year PFS 94% vs. 91%) or improved survival (2‐year survival 97% vs. 99%) 118 …”
Section: Management Of Tki Resistancementioning
confidence: 95%
“…Among patients with T315I vs. 99%). 118 Asciminib was also approved for patients with T315I mutation based on a separate report, where 52 patients with CML-CP and T315I mutation who failed ≥2 prior TKIs received asciminib 200 mg twice daily (31 patients had prior ponatinib exposure, of whom 15 had ponatinib resistance). 119 The estimated 2-year MMR rate was 57.8% in the ponatinib-naïve patients and 28.6% in ponatinib-treated patients.…”
Section: Second and Third Generation Tkismentioning
confidence: 99%
“…Asciminib is another TKI recently approved for patients who have failed two TKIs or more, based on higher response rates in comparison with bosutinib, with overall 6‐month MMR rates of 26% versus 13% and cumulative 2‐year MMR rates of 38% and 16%, respectively, after a median follow‐up of 2.3 years 15,16 . However, in the third‐line setting, no difference was seen in the rate of MMR at 12 months between asciminib and bosutinib (31% versus 27%) 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Other options available as third‐line therapy include the third‐generation BCR::ABL1 TKIs like ponatinib, the novel third‐generation TKIs like asciminib and the investigational TKI olverembatinib 13–15 . Asciminib was approved in 2021 for third‐line therapy of CML‐CP, based on a randomized trial comparing it with bosutinib, which showed a higher rate or major molecular response (MMR; BCR::ABL1 transcript levels <0.1% by the International Scale [IS]) with asciminib (6‐month MMR 25% versus 11.9%) 15,16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation